Employment of popular proverbs in Andalusian poetry In the fifth century AH - Hattab , Salman; Mari , Rodan; Kababah , Ghousen (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of the research was to find some Andalusian poems in the fifth century AH, in an attempt to uncover the effect of proverbs. The proverbs, as a component of culture, were present in Andalusian poetry and were a rich source of literary experience for the Andalusian poet. The human experience, which is a key to the completion of self-experience, he borrowed from the proverbs and represented in the construction of the text with the intention and awareness in advance in the retrieval of this cultural literary stock, which led to the emergence of his poems in a true social, and linked to the spirit of society, See the aesthetic dimension through the technical value and meaning who give the connotation and communication with the heritage in the composition of the optimal method.